THE ROLE OF EMERGENCY RESPONSE MOBILE REGIMENT (BRIGADE) OF THE NATIONAL GUARD OF UKRAINE IN A SPECIAL OPERATION DURING THE INTERNAL ARMED CONFLICT - Lavnichenko, О. V.; Hodlevskyi, S. О. (Honor and Law, 2019)
On the basis of current legislation analysis and regarding the character of National Guard of Ukraine tasks has been substantiated the role of emergency response mobile regiment (brigade) in localization and liquidation of an internal armed conflict.